A Trend for Increased Risk of Revision Surgery due to Deep Infection following Fast-Track Hip Arthroplasty - Einar Amlie; Anners Lerdal; Caryl L. Gay; Øystein Høvik; Lars Nordsletten; Sigbjørn Dimmen (Advances in Orthopedics)
Rates of revision surgery due to deep infection following total hip arthroplasty (THA) increased at a Norwegian hospital following implementation of fast-track procedures. The purpose of this study was to determine whether selected demographic (age and sex) and clinical (body mass index, American Society of Anesthesiologists (ASA) classification, surgery duration, length of hospital stay, cemented versus uncemented prosthesis, and fast-track procedures) factors were associated with higher risk of revision surgery due to deep infection following THA. In a prospective designed study 4,406 patients undergoing primary THA between January 2001 and January 2013 where included. Rates of infection-related revision surgery within 3 months of THA were higher among males and among patients who received fast-track THA. Adjusting for sex and age, the implemented fast-track elements were significantly associated with increased risk of revision surgery. Risk of infection-related revision surgery was unrelated to body mass index, physical status, surgery duration, length of hospital stay, and prosthesis type. Because local infiltration analgesia, drain cessation, and early mobilization were introduced in combination, it could not be determined which component or combination of components imposed the increased risk. The findings in this small sample raise concern about fast-track THA but require replication in other samples.